2013
DOI: 10.4103/0972-5229.112143
|View full text |Cite
|
Sign up to set email alerts
|

Multivisceral organ failure related to leptospirosis in pregnant patient

Abstract: Leptospirosis is the most widespread zoonosis in the world. It is caused by pathogenic leptospira infection. This infection is also an uncommon cause of hepatorenal failure. Indeed, hemolysis, elevated liver enzyme levels and low platelet count syndrome, and acute fatty liver of pregnancy are specific to the pregnant state. Leptospirosis is rarely described in pregnancy; it might mimic puerperal sepsis or hepatorenal failure associated with pregnancy induced hypertension. We report a case of leptospirosis pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Conjunctival suffusion is common and can be a useful clinical sign in early recognition. 2 Our patient had vomiting, dry cough, watery stools for a few days and hemoptysis, vaginal spotting, and breathing difficulty on the day of admission. She did not give a history of fever.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Conjunctival suffusion is common and can be a useful clinical sign in early recognition. 2 Our patient had vomiting, dry cough, watery stools for a few days and hemoptysis, vaginal spotting, and breathing difficulty on the day of admission. She did not give a history of fever.…”
Section: Discussionmentioning
confidence: 71%
“…Leptospirosis has a 5 to 40% mortality rate in severe disease. 2,3,4 Thrombocytopenia suggests severe disease and the subsequent risk of severe bleeding. 2,6 Wagenaar et al 6 have reported patients with leptospirosis may develop a spectrum of clinical effects due to infection-associated activation of the coagulation cascade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human infections can occur by direct contact with urine or tissue of an infected animal, especially rodents or indirectly through contaminated water, soil, or vegetation [1]. Leptospirosis ranges in severity from a mild illness suggesting a viral infection to a multisystemic syndrome.…”
Section: Discussionmentioning
confidence: 99%